2023
DOI: 10.1021/acs.macromol.3c00795
|View full text |Cite
|
Sign up to set email alerts
|

Effective Design for Long-Range Polymer Ordering Using Triptycene-Containing Side Chains

Abstract: Spontaneous long-range structural ordering of polymers can lead to improvements in their physical properties and the emergence of functions that cannot be expected in their amorphous states. We have demonstrated a design strategy to achieve structuring of various polymers using a particular type of triptycene, capable of forming a two-dimensional assembly. In this study, we investigated what designs are effective for achieving long-range polymer ordering by incorporating this triptycene motif into the side cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…By reacting these methoxy-substituted triptycenes with boron tribromide, we have shown that 1,8-dihydroxy and 1,8,13-trihydroxytriptycenes (166, 167) can be synthesized [11,77]. A wide variety of substituents can be introduced to these hydroxylated derivatives via ether linkages, and the resulting alkoxytriptycenes have been found to exhibit particular 2D assembly properties [11,[77][78][79][80][81]], which will be described in detail later. The various 1,8(,13)-substituted derivatives developed thus far include those with terminal olefin moieties (168, 171, 172) [77,80,81] and acryloyl groups (169) Recent advances in structurally elaborate triptycenes, triptycene-containing polymers and assemblies:.…”
Section: Synthetic Routes For Accessing Triptycene Derivatives and Tr...mentioning
confidence: 91%
See 4 more Smart Citations
“…By reacting these methoxy-substituted triptycenes with boron tribromide, we have shown that 1,8-dihydroxy and 1,8,13-trihydroxytriptycenes (166, 167) can be synthesized [11,77]. A wide variety of substituents can be introduced to these hydroxylated derivatives via ether linkages, and the resulting alkoxytriptycenes have been found to exhibit particular 2D assembly properties [11,[77][78][79][80][81]], which will be described in detail later. The various 1,8(,13)-substituted derivatives developed thus far include those with terminal olefin moieties (168, 171, 172) [77,80,81] and acryloyl groups (169) Recent advances in structurally elaborate triptycenes, triptycene-containing polymers and assemblies:.…”
Section: Synthetic Routes For Accessing Triptycene Derivatives and Tr...mentioning
confidence: 91%
“…8) and n-butyl acrylate (Fig. 23a) [78]. The thermal stability of these triptycene-containing copolymers is comparable (2% weight loss temperature: ca.…”
Section: Nonporous 2d Assemblies and Polymersmentioning
confidence: 92%
See 3 more Smart Citations